ANALISIS FAKTOR-FAKTOR PENYEBAB STRES KERJA PADA STAF REKAM MEDIS DI RUMAH SAKIT UMUM DAERAH KOTA MATARAM - Juli Ardani (Master of Management, Mataram University, 2017)
Stress is the feeling made when the individual react on a certain case. This is the way one grows to fight against threat and constraints by focusing, preparing strength, stamina, and watchfulness. Stress may be good or bad for employees. The work efficiency depends very much on the good mental and physical condition of the employees. This research is aimed at identifying and analyzing the factors causing job stress of employees working at the medical records at Mataram District Hospital. The population of this research is all 57 employees working at instalation of medical records. The study has beenrestricted to medical records only, due to accessibility, time and other related factors The data were collected through questionnaires, interview and documentation. The data analysis is using factor analysis. The research showed that there are three factors casing work stress. The first is the uncertainty of economy, organizational structure, organizational leadership, and personal characteristics. Second is job demand, role demand,, and personal demand. Third is technology changes and family problem. The result of this research may be useful for the authority of the hospital to make decision in relation to human recourses and also for all staffs in general and the staffs of medical records in particular, especially in recruiting the employees. Keywords: job stress, hospital, employees of medical records, factor analysis.